A novel cell senescence-related IncRNA survival model associated with the tumor immune environment in colorectal cancer - Xu, Chengfei; Li, Fanghan; Liu, Zilin; Yan, Chuanjing; Xiao, Jiangwei (Frontiers in Immunology, 2022)
Abstract Long noncoding RNAs have a major role in tumorigenesis, development, and metastasis in colorectal cancer (CRC), participate in the regulation of cell senescence, and are related to the prognosis of CRC. Therefore, it is important to validate cell senescence-related lncRNAs that correlate with prognosis in CRC. Methods CRC expression profile data and clinical information were downloaded from TCGA. A gene list related to cellular senescence was obtained from Human Aging Genomic Resources. A coexpression network of cell senescence-related mRNA‒lncRNA was explored with R. Six cell senescence-related lncRNA signatures were identified by univariate and multivariate analyses. The cell senescence-related risk model was generated by using six cell senescence-related lncRNAs, and the risk score was calculated. Furthermore, an internal validation set and GSE17537 were used to verify the risk model. The risk model demonstrated good stability and accuracy. Finally, we investigated the correlation between cell senescence-related risk scores and immune infiltration, immune function, immune checkpoints, and drug sensitivity. Result We established a signature of six cell senescence-related lncRNAs. The cell senescence-related risk model revealed an exceptional ability to assess the prognosis of colorectal cancer and was correlated with clinical features. Additionally, we observed that risk models correlate with the tumor microenvironment and immune checkpoints, potentially predicting patient response to clinical immunotherapy. Finally, we validated the correlation between the cell senescence-related risk model and drug susceptibility. Our findings indicated that AICAR, cisplatin, nilotinib, and bexarotene exhibited lower IC50 values in the high-risk group. Conclusion Our current study identified 6 cell senescence-associated lncRNA signatures that may be vital biomarkers to predict the prognostic features and immune and chemotherapy responses in CRC.